2016
DOI: 10.1093/icb/icw083
|View full text |Cite|
|
Sign up to set email alerts
|

Resources and Recommendations for Using Transcriptomics to Address Grand Challenges in Comparative Biology

Abstract: High-throughput RNA sequencing (RNA-seq) technology has become an important tool for studying physiological responses of organisms to changes in their environment. De novo assembly of RNA-seq data has allowed researchers to create a comprehensive catalog of genes expressed in a tissue and to quantify their expression without a complete genome sequence. The contributions from the “Tapping the Power of Crustacean Transcriptomics to Address Grand Challenges in Comparative Biology” symposium in this issue show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Transcriptomics and proteomics have revolutionized crustacean physiology ( 22 , 23 ). These approaches have shown that the YO undergoes molt stage-specific changes in phenotype that differ quantitatively and qualitatively in mRNA and protein levels ( 2 , 16 , 21 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomics and proteomics have revolutionized crustacean physiology ( 22 , 23 ). These approaches have shown that the YO undergoes molt stage-specific changes in phenotype that differ quantitatively and qualitatively in mRNA and protein levels ( 2 , 16 , 21 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus is native to Asia (Karge and Klotz 2013) and typically used there as a model organism in ecotoxicology (EPA/ ROC 2013) due to its wide distribution in lakes, streams and ponds (de Grave et al 2008;Karge and Klotz 2013;Kohal et al 2018), adaptation to diverse water parameters, relatively short reproduction period and sensitivity to endocrine disrupting chemicals (Huang et al 2006;Mykles et al 2016;Huang et al 2020). Besides, the freshwater organism is increasingly used to address questions relating to decapod physiology (Sonakowska et al 2015(Sonakowska et al , 2016Włodarczyk et al 2017) and genomics (Mykles and Hui 2015;Mykles et al 2016). Today, it has been found in European rivers (Klotz et al 2013;Jabłońska et al 2018), most likely as a result of global trade as an exotic species for hobby aquarists and the unintentional release into the aquatic environment (Schoolmann and Arndt 2018;Jaskuła et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of transcriptome data is highly exploited to understand gene functionality and expression mechanisms in different tissues in various conditions [136][137][138]. Due to the general importance of transcriptomic data to depict gene expression patterns and to infer on gene control and regulatory mechanisms of cell functionality, the processes involved in plant responses to abiotic stress are being largely investigated at the transcriptome level through microarray and RNA sequencing analyses, such as expressed sequence tags (ESTs) and RNA-seq [32,44,[139][140][141].…”
Section: Transcriptomicsmentioning
confidence: 99%